Political economy of adult learning systems : comparative study of strategies, policies and constraints - Desjardins, Richard [Verfasser] (My University, 2018)
"Based on comparative adult education statistics offered by the Organisation for Economic Co-operation and Development (OECD) Survey of Adult Skills (PIAAC) and country case studies, this book analyses the policies and structures that foster adult learning. It examines a variety of forms of adult learning, ranging from initial forms of post-compulsory education, such as upper secondary tracks and tertiary education, to firm training, compensatory adult education and learning for civic and leisure oriented purposes. Throughout the book, adult learning systems are directly linked to a variety of structural and public policy frameworks using a comparative welfare state approach. Themes such as pathways to learning and transition systems, participation patterns in higher education and participation patterns in other organized forms of adult learning are covered. The countries discussed are the UK, the USA, Korea, Denmark, Finland, Norway, Germany and the Netherlands. Situated at the intersection between scholarship and policy and using a mixed-methods approach, this title contributes fundamental insights into the further study of policies and structures related to alternative post-compulsory learning pathways." (Publisher, BIBB-Doku)
Keywords: S 1.5 Weiterbildung; S 2.3 Berufsbildungspolitik; G 2.2.4 Lebensbegleitendes & lebenslanges Lernen; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; G 1.1.4 Statistiken zu speziellen Problemlagen & Bereichen; I 2.1 Deutschland; I 2.2.1 Westeuropa; I 2.3.2 Nordamerika; I 2.3.4 Asien; Erwachsenenbildung; Berufliche Weiterbildung; Weiterbildungssystem; Weiterbildungspolitik; Lebenslanges Lernen; Weiterbildungsbeteiligung; Weiterbildungsstatistik; PIAAC; Internationaler Vergleich; Bundesrepublik Deutschland; Dänemark; Finnland; Norwegen; Vereinigtes Königreich; USA; Korea